A Fast Postprocessing Algorithm for the Overlapping Problem in Wafer Map Detection. (13th December 2021) - Li, Yang; Wang, Jianguo
Abstract : Mixed defects have become increasingly popular in defect detection and one of the hottest research areas in wafer maps. Postprocessing methods used to solve the overlapping problem in mass mixed defects have a poor detection speed, which is insufficient for rapid defect detection. In this paper, the fast-soft nonmaximum suppression (fs-NMS) method is proposed to solve this problem. The score of the detection box is updated by optimizing the penalty distribution function. Further, this paper analyzes the performance of the fs-NMS method in wafer defect detection. As a penalty, the logistic function is used, and experiments are conducted using single-stage and two-stage detectors. The final results show that, compared to the soft-NMS, the efficiency for the single-stage and two-stage detectors is increased on average by 9.63% and 21.72%, respectively.